2017
DOI: 10.3846/20294913.2016.1213192
|View full text |Cite
|
Sign up to set email alerts
|

Bank Profitability and Macroeconomy: Evidence From Lithuania

Abstract: Abstract. The purpose of this paper is to investigate the relationship between profitability of the Lithuanian banking sector and its internal and external determinants. We use the panel error correction model to assess long-term and short-term determinants of items from bank income statements (net interest income, net fee and commission income and operating expenses). The results of the pooled mean group estimator show that bank size and real GDP are the main determinants in the long-term. Meanwhile, empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Claeys and Vennet (2004) showed that the concentration ratio of the banking markets was positively linked to profitability for Western European banks but was not validated for Eastern European banks. Naruševičius (2018) found no significant relationship between the concentration ratio of the banking sector and banking profitability in Lithuania. However, Athanasoglou et al (2008) found no clear results for this relationship.…”
Section: Literature Reviewmentioning
confidence: 74%
See 1 more Smart Citation
“…Claeys and Vennet (2004) showed that the concentration ratio of the banking markets was positively linked to profitability for Western European banks but was not validated for Eastern European banks. Naruševičius (2018) found no significant relationship between the concentration ratio of the banking sector and banking profitability in Lithuania. However, Athanasoglou et al (2008) found no clear results for this relationship.…”
Section: Literature Reviewmentioning
confidence: 74%
“…The unemployment rate was found to be one of the most significant macroeconomic variables for the banking performance in the CEE banking systems. The unemployment rate dynamic is important for the banking operating expenses (negotiating salaries) and, thus, for the banking profitability; hence, a positive relation with banking profitability was demonstrated for the Lithuanian banking sector based on a pooled mean group estimation technique (Naruševičius 2018). Clair (2004) studied the banking system in Singapore and determined that the unemployment rate influenced the stability and performance of the local banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The largest portions of these studies are devoted to analysing the profitability determinants of banks which operated in a specific country. Examples of these single-country research studies are those for the USA (Chaudhry et al , 1995; Tregenna, 2009; Hoffmann, 2011; Kanas et al , 2012; Chronopoulos et al , 2015; Ding et al , 2017), UK (Kosmidou et al , 2005; Saeed, 2014), Japan (Liu and Wilson, 2010), Spain (Trujillo-Ponce, 2013), Italy (Albertazzi et al , 2016), India (Badola and Verma, 2006; Manoj, 2010; Bhatia et al , 2012; Sufian and Noor, 2012; Karimzadeh et al , 2013; Sinha and Sharma, 2016; Davis and Mathew, 2017), China (Garcia-Herrero et al , 2009; Heffernan and Fu, 2008; Garcia-Herrero et al , 2009; Tan and Floros, 2012; Lee and Hsieh, 2013; Yin and Matthews, 2016; Ding et al , 2017; Tan et al , 2017), Hong Kong (Jiang et al , 2003), Switzerland (Dietrich and Wanzenried, 2011), Brazil (Afanasieff et al , 2002), Latvia (Jurevičienė et al , 2015), Lithuania (Jurevičienė et al , 2015; Naruševicius, 2018), Greece (Mamatzakis and Remoundos, 2003; Athanasoglou et al , 2005; Alexiou and Sofoklis, 2009), Turkey (Sayilgan and Yildirim, 2009; Alper and Anbar, 2011; Akbaş, 2012; Macit, 2012; Acaracvi and Calim, 2013, Ayaydın and Karakaya, 2014; Turgutlu, 2014; Ozgur and Gorus, 2016; Topak and Talu, 2017), Albania (Duraj and Moci, 2015), Vietnam (Le, 2017), Mauritius (Bhavish et al , 2017), Nigeria (Obamuyi, 2013; Chidozie and Ayadi, 2017; Ebenezer et al , 2017), Ethiopia (Rani and Zergaw, 2017; Akinkunmi, 2017), Pakistan (Gul et al , 2011; Sohail et al , 2013; Kanwal and Nadeem, 2013; Shoaib et al , 2015), Bangladesh (Majumder and Uddin, 2017), Tunisia (Bougatef and Bougatef, 2017), Indonesia (Agustini and V...…”
Section: Literature Overviewmentioning
confidence: 99%
“…The bank characteristics include bank size, leverage, and profitability. Larger banks are set to gain from the economics of scale, offer more products to their customers, and have more cross-selling opportunities (Naruševičius, 2018;Phan et al, 2019;Rogers and Sinkey, 1999). Therefore, larger banks tend to offer lower deposit rates and charge higher retail fees than smaller banks (Tennant and Sutherland, 2014).…”
Section: Methodsmentioning
confidence: 99%